Effect Of Acidic Calcium Phosphate Solution Concentration On The Setting Properties Of Porous Β-Tricalcium Phosphate Granular Cement - Mohd Ariffin, Mohamad Fadhlin (Universiti Sains Malaysia, 2018)
The purpose of this study is to fabricate porous β-tricalcium phosphate granular cement by exposing β-TCP granules (300-600 µm) with different concentration of acidic calcium phosphate solution. β-tricalcium phosphate granules were exposed to 1.0 mol/L phosphoric acid, 1 mol/L H3PO4-0.2 mol/L, 1 mol/L H3PO4-0.8 mol/L and 1 mol/L H3PO4-1.4 mol/L MCPM with liquid to granular ratio (L/G) of 1:1respectively. Besides, the setting time used in this study were fixed at 1,5,10,30 and 50 minutes respectively. The set specimen was characterized by XRD to detect the formation of dicalcium phosphate dihydrate (DCPD) phase in the set specimen. It was found that when high concentration of acidic calcium phosphate solutions was used, more DCPD formation were observed. This finding consistent with XRD result which the DCPD amount for 1.4 mol/L MCPM -1.0 mol/L phosphoric acid is higher than the 0.2 mol/L MCPM -1.0 mol/L phosphoric acid. SEM result demonstrated that more DCPD crystal were interlocked each other when increased concentration of acidic calcium phosphate solution. The high amount of interlocked DCPD crystal will increased the compression strength of set specimen. 1.4 mol/L MCPM -1.0 mol/L phosphoric acid shows the lowest porosity which is 74.5% and high compression strength which is 5.86 MPa in comparison with other concentration. Therefore, it shows that increasing of acidic calcium phosphate solution concentration will affected the setting properties of porous β-tricalcium phosphate EFFECT OF ACIDIC CALCIUM PHOSPHATE SOLUTION CONCENTRATION ON THE SETTING PROPERTIES OF POROUS -TRICALCIUM PHOSPHATE GRANULAR CEMENT β granular cement which the cement is fully set at 5 minutes which in the range of ample time.